Pitfalls and errors of HPLC in pictures - Meyer, Veronika (Weinheim : Wiley-VCH, 2013)
The third edition of this popular problem-solving guide for this widely-used method includes eleven completely new examples and several updated ones, adding up to over 100 potential pitfalls and errors in HPLC. Each example is presented on a double page with the text on the left-hand and a figure on the right-hand side, true to the motto ""a picture says more than a thousand words"". In addition, the author presents essential fundamentals as well as helpful strategies, such as equipment tests or quality assurance processes. A must-have resource for all those users without a background in an analytical chemistry -- showing how to use HPLC efficiently and obtain correct results.
pt. 1. Introduction -- pt. 2. Pitfalls and sources of error -- pt. 3. Useful strategies.
Includes index.
Keywords: High performance liquid chromatography; Chromatography, High Pressure Liquid; High performance liquid chromatography -- Industrial applications; SCIENCE -- Chemistry -- Analytic; High performance liquid chromatography; Electronic books